Strategies for Efficient Gene Editing in Protoplasts of Solanum tuberosum Theme: Determining gRNA Efficiency Design by Utilizing Protoplast (Research) - Frida Meijer Carlsen; Ida Elisabeth Johansen; Ida Elisabeth Johansen; Zhang Yang; Ying Liu; Ying Liu; Ida Nøhr Westberg; Nam Phuong Kieu; Bodil Jørgensen; Marit Lenman; Erik Andreasson; Kåre Lehmann Nielsen; et al. (Frontiers in Genome Editing, 2022)
Potato (Solanum tuberosum) is a highly diverse tetraploid crop. Elite cultivars are extremely heterozygous with a high prevalence of small length polymorphisms (indels) and single nucleotide polymorphisms (SNPs) within and between cultivars, which must be considered in CRISPR/Cas gene editing strategies and designs to obtain successful gene editing. In the present study, in-depth sequencing of the glucan water dikinase (GWD)1 and the downy mildew resistant 6 (DMR6-1) genes in the potato cultivars Saturna and Wotan, respectively, revealed both indels and a 1.3–2.8 higher SNP prevalence when compared to the heterozygous diploid RH genome sequence as expected for a tetraploid compared to a diploid. This complicates guide RNA (gRNA) and diagnostic PCR designs. High editing efficiencies at the cell pool (protoplast) level are pivotal for achieving full allelic knock-out in tetraploids and for reducing the downstream cumbersome and delicate ex-plant regeneration. Here, CRISPR/Cas ribonucleoprotein particles (RNP) were delivered transiently to protoplasts by polyethylene glycol (PEG) mediated transformation. For each of GWD1 and DMR6-1, 6–10 gRNAs were designed to target regions comprising the 5′ and the 3′ end of the two genes. Similar to other studies including several organisms, editing efficiency of the individual RNPs/gRNAs varied significantly, and some generated specific indel patterns. While RNPs targeting the 5′ end of GWD1 yielded significantly higher editing when compared to targeting the 3′ end, editing efficiencies in the 5′ and 3′ end of DMR6-1 appeared to be somewhat similar. Simultaneous targeting of either the 5′ or the 3′ end with two RNPs (multiplexing) yielded a clear positive synergistic effect on the total editing when targeting the 3′ end of the GWD1 gene only. Multiplexing of the two genes, residing on different chromosomes, yielded no or slightly negative effects on the individual RNP/gRNA editing efficiencies when compared to editing efficiencies obtained in the single RNP/gRNA transformations. These initial findings may instigate larger studies needed for facilitating and optimizing precision breeding in plants.